Impact of leaflet trichomes on settlement and oviposition of Tetranychus evansi (Acari: Tetranychidae) in African and South American tomatoes - Savi, P. J. [UNESP]; Moraes, G. J. De; Junior, A. L. Boiça [UNESP]; Melville, C. C. [UNESP]; Carvalho, R. F. [UNESP]; Lourenção, A. L.; Andrade, D. J. [UNESP] (Systematic and Applied Acarology Society, 2019)
Red spider mite (Tetranychus evansi) is considered one of the main tomato pests in Africa. As an alternative to chemical control, the use of pest-resistant cultivars has been considered a desirable and environment-friendly choice. Therefore, our study aimed to evaluate the influence of trichomes on settlement and oviposition preferences of T. evansi in African tomato varieties, besides comparing them to South American wild tomato species. First, free-and no-choice laboratory tests were carried out to investigate settlement and oviposition preferences of females on leaflets of two South American wild tomato species (Solanum pennellii LA-716 and S. habrochaites var. hirsutum PI134417) and five African tomato varieties (S. lycopersicum cv. Kekefo, Akikon, TLCV15, Tounvi, and TOML4), the latter are widely grown in Benin. Thereafter, leaf trichome types were determined and densities were estimated and then correlated to numbers of settled females and laid eggs on leaflets of each assessed genotype. According to our findings, females strongly preferred to settle and oviposit on African varieties rather than on South American genotypes. Regarding trichome density, non-glandular type Va showed significant positive correlations with both studied parameters, with the highest amounts in African genotypes. Conversely, glandular trichome density (mainly types I, IV, and VI) presented significant negative correlations with preference indicators, with the largest densities in South American species. The high density of non-glandular trichomes on leaflets of the varieties Akikon, Tounvi, Kekefo, TOML4, and TLCV15 might have been one of the causes of preference of T. evansi females.
Keywords: Herbivory; Plant Resistance; Red spider mite; Solanum